Neuroprotective Effect of Placental Factors in Model of Glutamate Induced Toxicity in Newborn Rat Brain Cells - Chub, Oleg V.; Shevchenko, Mariya V.; Prokopyuk, Vladimir Yu. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):176.